2017
DOI: 10.3389/fncel.2017.00080
|View full text |Cite
|
Sign up to set email alerts
|

ALS Pathogenesis and Therapeutic Approaches: The Role of Mesenchymal Stem Cells and Extracellular Vesicles

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease characterized by progressive muscle paralysis determined by the degeneration of motoneurons in the motor cortex brainstem and spinal cord. The ALS pathogenetic mechanisms are still unclear, despite the wealth of studies demonstrating the involvement of several altered signaling pathways, such as mitochondrial dysfunction, glutamate excitotoxicity, oxidative stress and neuroinflammation. To date, the proposed therapeutic strategies are tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
117
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(127 citation statements)
references
References 144 publications
0
117
0
4
Order By: Relevance
“…Wang, Ma, et al, 2018) Bone and cartilage diseases (Jo et al, 2014;Kastrinaki et al, 2013) Autoimmune diseases (Xu, 2018;W. Zhang, Feng, et al, 2018) Amyotrophic lateral sclerosis (Bonafede & Mariotti, 2017) Diabetes (Evangelista et al, 2018;Gabr et al, 2018) Glaucoma (Manuguerra-Gagne et al, 2013;Osborne, Sanderson, & Martin, 2018;Roubeix et al, 2015) Graft vs host disease (Jurado et al, 2017;Zhao et al, 2015) Intervertebral disc disease (Ahn et al, 2015;Beeravolu et al, 2018;Pereira et al, 2016;Perez-Cruet et al, 2018) Multiple sclerosis (Harris et al, 2018;Nasri et al, 2018;Planchon et al, 2018) Myocardial infarction ( investigated for the treatment of chronic tissue ulcers caused by diabetes. Patients were administered with MSCs for skin healing showed an improvement in microvascularisation structure (Kirana et al, 2012).…”
Section: Promising Applications Referencementioning
confidence: 99%
See 1 more Smart Citation
“…Wang, Ma, et al, 2018) Bone and cartilage diseases (Jo et al, 2014;Kastrinaki et al, 2013) Autoimmune diseases (Xu, 2018;W. Zhang, Feng, et al, 2018) Amyotrophic lateral sclerosis (Bonafede & Mariotti, 2017) Diabetes (Evangelista et al, 2018;Gabr et al, 2018) Glaucoma (Manuguerra-Gagne et al, 2013;Osborne, Sanderson, & Martin, 2018;Roubeix et al, 2015) Graft vs host disease (Jurado et al, 2017;Zhao et al, 2015) Intervertebral disc disease (Ahn et al, 2015;Beeravolu et al, 2018;Pereira et al, 2016;Perez-Cruet et al, 2018) Multiple sclerosis (Harris et al, 2018;Nasri et al, 2018;Planchon et al, 2018) Myocardial infarction ( investigated for the treatment of chronic tissue ulcers caused by diabetes. Patients were administered with MSCs for skin healing showed an improvement in microvascularisation structure (Kirana et al, 2012).…”
Section: Promising Applications Referencementioning
confidence: 99%
“…In addition, MSCs have a paracrine effect that promotes immunomodulation as well as antiapoptotic and anti-oxidative effects, which can be helpful for treating neuromuscular pains (van Buul et al, 2014) and many other diseases (de Witte et al, 2018;Francois et al, 2013;Khubutiya, Vagabov, Temnov, & Sklifas, 2014). MSCs are also being investigated for their therapeutic potential to treat degenerative diseases and disorders such as Parkinson's disease (PD; Jamali, Ma Hattab, Amman, & Awidi, 2018; H. Kim, Lee, et al, 2018), Alzheimer's disease (AD; Cui et al, 2017;Han et al, 2018), amyotrophic lateral sclerosis (Bonafede & Mariotti, 2017), multiple sclerosis (MS; Harris et al, 2018; Nasri Ahn et al, 2015;Beeravolu et al, 2018;Perez-Cruet et al, 2018), retinal degenerative disease (RDD; Y. Wang, Zhang, Shen, Zhang, & Gu, 2018;, myocardial infarction (X. Q.…”
mentioning
confidence: 99%
“…Current studies have revealed that EVs act on target cells by fusing with the target membrane to enter the cell and release the cellular contents, interacting with the receptor-ligand, and inducing the target cells to ingest exosomes via endocytosis [61,62]. Accumulating evidence has shown that MSC-derived EVs effectively restore injured organs and tissues, such as the kidneys, heart, liver, and brain, in animal models, and the substance contained in EVs may play a role in their functioning [60,63,64]. Wang et al [65] reported that MSC-derived EVs significantly promoted angiogenesis and cardiac function via miR-210 in a mouse myocardial infarction model.…”
Section: Msc-derived Evs: a Therapeutic Vector Of Mscs?mentioning
confidence: 99%
“…The roles of exosomes and their biologic effects may depend on the origin and functional status of the parental cells, which to a large degree affects the contents of the exosome cargo to be delivered to the recipient or target cells . Despite the various physiological effects that exosomes exert, exosomes may also be associated with inflammation, angiogenesis, and apoptosis and promote pathogenesis of tumors or other diseases . It has been reported that exosomes are paracrine regulators of the tumor microenvironment and contain complex cargo .…”
Section: Exosomes: Basic Biologymentioning
confidence: 99%
“…34 Despite the various physiological effects that exosomes exert, exosomes may also be associated with inflammation, angiogenesis, and apoptosis and promote pathogenesis of tumors or other diseases. [41][42][43][44] It has been reported that exosomes are paracrine regulators of the tumor microenvironment and contain complex cargo. 45 Exosomes secreted from acute myeloid leukemia cells carry miR-150 and miR-155, which suppress the function of hematopoietic stem and progenitor cells.…”
Section: Biological Function and Physiologic And Pathologic Effectsmentioning
confidence: 99%